Review of Armenia’s Experience with Water Public-Private Partnerships - Marin, Philippe; Muzenda, Dambudzo; Andreasyan, Andranik (World Bank, Washington, DC, 2017)
This report analyzes four water public private partnerships (PPPs) undertaken in Armenia between 2000 and 2016 and the start of a national water lease contract that began in January 2017. It provides an overview of each of the four first generation PPPs. It explains the steps taken by the Government of Armenia to create an enabling environment for the PPPs, including the decision-making process. The report also provides comparable details on how each PPP contract was designed and implemented, including the following parameters: tendering, contract terms, capital investment program, financing, tariffs. The results obtained for each PPP are included, particularly operational results (continuity of water supply, electricity use, non-revenue water, etc.) and financial results (billing, revenues, subsidies, etc.). This analysis is provided in a succinct way, with main messages and lessons learned provided for each PPP contract and for the entirety of the PPP experience over the first 16 years. The report also discusses the new national lease contract, which builds directly on the experience of the first set of water PPPs. It concludes by reflecting on some key issues to be addressed as the new lease contract begins: the timely implementation of capital expenditure; provision of services to unserved communities; and expansion of wastewater collection and treatment.